Adolescent girls' Instagram and TikTok use: Examining relations with body image-related constructs over time using random intercept cross-lagged panel models. (June 2022) - Maes, Chelly; Vandenbosch, Laura
Abstract: The literature on body image ramifications of girls' uses of appearance-focused social media (ASM) is limited, and even non-existing in terms of TikTok uses. With this brief report, we aimed to fill this gap in the literature by analyzing three waves of data on girls' ASM use and body image-related constructs (i.e., internalization of beauty ideals and body image self-discrepancy) using random-intercept cross-lagged panel models (RI-CLPMs). The total sample consisted of 229 girls ( M age = 15.12, SD = 1.50). Controlling for age and body mass index (BMI), the RI-CLPMs revealed that neither TikTok nor Instagram were predictive of subsequent increases or decreases in internalization of beauty ideals and body image self-discrepancy. Lower scores on body image self-discrepancy at W2 (i.e., wanting to have a thinner body) did predict higher uses of Instagram at W3. No evidence for between-person effects was garnered. The results enrich our knowledge on long-term implications of girls' Instagram and TikTok use for their body image. They further underline the need for research that more specifically disentangles the role of different appearance-related activities on social media and their impact on girls' body image constructs. Highlights: Neither TikTok use nor Instagram use predicted body image-related outcomes over time. Body image self-discrepancy at W2 predicted increases in girls' Instagram uses five months later (W3). No evidence for between-person level relations was garnered.